A cohesive zone model approach to interlaminar behaviour of carbon/epoxy laminated curved beams. (15th April 2020) - Ranz, David; Cuartero, Jesus; Castejon, Luis; Miralbes, Ramon; Malon, Hugo
Abstract: This study analytically investigates the behaviour of carbon/epoxy laminated curved beams subjected to interlaminar tensile stress by means of a four-point-bending test, carried out in compliance with ASTM D6415 Standard. A Cohesive Zone Model (CZM) has been used to analyse the interlaminar tensile strength (ILTS) and the post-failure behaviour for lay-ups in several thicknesses, as well as the location of first and subsequent predicted delamination. In this study, the model behaviour is described by a bilinear constitutive model. Initially, a law of traction-separation governs the elastic behaviour, until satisfying a quadratic criterion that establishes the failure and degradation starting at the interface. Finally, a law describes the evolution of the damage and the interaction in mixed-mode conditions, which leads to the final failure of the interface and delamination onset. Two-dimensional finite element models (FEM) have been created to apply the CZM and analyse the influence of several cohesive model parameters, such as, cohesive element stiffness, cohesive element size and critical energy release rate. Predicted load–displacement curves have been compared with the experimental results obtained and strong correlation has been observed. The ILTS values predicted by the two-dimensional models show deviations no greater than 5.6% in comparison with the experimental results. These models and the influence of their parameters play an important role in the prediction of the interlaminar tensile strength and the post-failure behaviour of laminated curved beams.